HRM practices and performance management in public service organizations in Bangladesh: An empirical study - Khan, Mohammad Aktaruzzaman; Hoque, Nazamul; Shahabuddin, AM (IIUC Studies, 2020)
This paper assesses the effects of HRM practices on the management performance of public service organizations as public service is believed to safeguard the national property for allocating goods and services timely, and reasonably to the inhabitants of the country especially in a developing country like Bangladesh. The question circling whether the HR practices in public service are sincere for equal and equitable distribution of products and services effectively. In doing so, this study investigated the effectiveness of HR practices and methods on the performance management of public service. The study, through a mixed-method approach, conveniently surveyed a sample of 142 respondents and interview drawn from seven key informants of two Bangladesh Civil Service (BCS) cadre from Chittagong, the second-largest city of the country. The study shows the differences in the effects of HRM practices that employee training positively and commensurate compensation negatively predict employee performance, respectively, however, performance appraisal feedback is not a significant predictor. The study drawn the implications for HRM practices in BCS organization and encouraged future scholars to further examine these differences. IIUC Studies Vol.16, December 2019: 9-34